A Mosaic of Suburbs: The Historic Boroughs of Palermo. (November 2013) - Picone, Marco; Schilleci, Filippo
Palermo suburbs have grown and developed at the expense of becoming isolated from other parts of the city. Ancient boroughs have been eradicated, alongside their urban identities. The challenges of a cosmopolitan and global world are felt even in middle-sized, fringe cities like Palermo, as its suburbs are forced to become tiles of an urban mosaic that is created by urban development. It is the duty of urban scholars to clarify and strengthen the relationships between these urban parts, and in the process restore the neglected notion of neighborhood . By overcoming the distinction between cities and urban sprawl, the controversial dispute may be resolved by urban scholars. Through historical and social analyses, this article outlines two possible transformations the boroughs can take: either as outskirts or as neighborhoods .